Armand-Jean de Rancé, On Receivin, Jesus Christ: Two Conferences for Christmas - Bell, David N. (Cistercian studies quarterly, 2025)
The article discusses Armand-Jean de Rancé's conversion to a deeply Christocentric life after the death of his mistress and his theological reflections in his conferences for Christmas. Topics include the necessity of divine grace in preparing the heart for Christ, the paradox of Christ receiving himself within believers, and the significance of properly fulfilling one's spiritual duties.